2005
DOI: 10.1631/jzus.2005.b0897
|View full text |Cite
|
Sign up to set email alerts
|

Resistin levels of serum and follicular fluid in non-obese patients with polycystic ovary syndrome during IVF cycles

Abstract: Abstract:Objectives: To measure serum and follicular resistin, steroids hormone levels in women with PCOS (polycystic ovary syndrome) (BMI (body mass index)<25 kg/m 2 ), to assess possible correlations of resistin to hormonal and metabolic parameters and to analyze the clinical outcomes of in vitro fertilization-embryo transfer (IVF-ET) in women with PCOS and tubal infertility. Study design: We analyzed the clinical outcomes of IVF-ET in women with PCOS (BMI<25 kg/m 2 ) and tubal infertility during the years 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
12
0
4
Order By: Relevance
“…doses, in accordance with the plasma resistin concentration in humans (5-15 ng/ml) (Lu et al 2005, Munir et al 2005, Asimakopoulos et al 2009). Moreover, our results are in agreement with an observation in human preadipocytes where resistin did not influence cell proliferation (Ort et al 2005).…”
Section: Resistin Decreases Ovarian Cell Apoptosissupporting
confidence: 60%
“…doses, in accordance with the plasma resistin concentration in humans (5-15 ng/ml) (Lu et al 2005, Munir et al 2005, Asimakopoulos et al 2009). Moreover, our results are in agreement with an observation in human preadipocytes where resistin did not influence cell proliferation (Ort et al 2005).…”
Section: Resistin Decreases Ovarian Cell Apoptosissupporting
confidence: 60%
“…As far as we are aware, the correlations between resistin and estrogen have not been evaluated in postmenopausal women. However, in adult women with polycystic ovary syndrome, serum levels of resistin and estradiol did not correlate significantly [40,41]. The sexual dimorphism in plasma resistin concentrations is probably caused by factors other than estrogens.…”
Section: Discussionmentioning
confidence: 81%
“…In contrary, Chen et al [2007] in a case-control study, reported a negative correlation between resistin levels and the number of oocytes retrieved, but similar fertilization rates, in 44 non-PCOS women undergoing IVF; authors suggested a direct link of high levels with poor ovarian response and attributed their findings to the direct effect of inflammatory cytokines on resistin production, cytokines which, per se, were implicated to the etiology of their subfertility [24]. Lu et al (2005), in a retrospective observational study, found no correlation between serum measurement on day 3 before stimulation and FF levels on fertilization, maturation, miscarriage and clinical pregnancy rates in 20 PCOS and 20 non-PCOS women undergoing IVF; authors concluded that resistin does not have any impact in steroidogenesis and oocyte development in this group of subfertile women [26]. Additionally, Seow et al [2005] in a prospective clinical trial, found no correlation between serum and FF resistin levels with pregnancy outcome in PCOS women on IVF [25].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment allocation was achieved according to the number of the file of each patient (0 to 3 vs. 4 to 9 as a last digit), respectively. In order to avoid potential sources of bias, we included participants who were referred to the Unit consecutively, and the number selected was based on previous reports [24][25][26]. The enrollment of the participants to the two protocols was based on the standard clinical practice of the Unit.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation